Composite vignettes of Swedish male and female professional handball players` career paths - Ekengren, J.; Stambulova, N. B.; Johnson, U.; Carlsson, I.-M.; Ryba, T. V. (Sport in Society: Cultures, Commerce, Media, Politics, 2020)
The aim of this study was to describe gender-specific career paths of Swedish professional handball players. A reanalysis of Ekengren et al. (2018) career interviews with nine male and nine female players led to creating two composite vignettes using the athletes` own words, accounted for typical features in the male and female players` career paths. Seven themes were identified in the analysis of the men`s transcripts and eight themes derived from the women`s transcripts. Further, the themes of both vignettes were aligned with career stages described in our previous study (Ekengren et al. 2018). The male players` vignette is interpreted as a performance narrative congruent with elite handball culture that promotes performance success and profitable professional contracts. The female players` vignette is more holistic, embracing handball, studies, motherhood, and how they ought to be as Swedish women. Recommendations for future research are provided.